Effectiveness of AbobotulinumtoxinA in Post-stroke Upper Limb Spasticity in Relation to Timing of Treatment - Wissel, Jörg; Fheodoroff, Klemens; Hoonhorst, Maurits; Müngersdorf, Martina; Gallien, Philippe; Meier, Niklaus; Hamacher, Jürgen; Hefter, Harald; Maisonobe, Pascal; Koch, Manuel (Frontiers in Neurology, 2020)
Background: Recent studies of botulinum toxin for post-stroke spasticity indicate potential benefits of early treatment (i.e. first 6 months) in terms of developing hypertonicity, pain and passive function limitations. This non-interventional, longitudinal study aimed to assess the impact of disease duration on the effectiveness of abobotulinumtoxinA treatment for upper limb spasticity. Methods: The early-BIRD study (NCT01840475) was conducted between Feb 2013 and Feb 2018 in 43 centers across Germany, France, Austria, Netherlands and Switzerland. Adult patients with post-stroke upper limb spasticity undergoing routine abobotulinumtoxinA treatment were followed for up to 4 treatment cycles. Patients were categorized by time from stroke event to first botulinum toxin-A treatment in the study (as defined by the 1st and 3rd quartiles time distribution) into early-, medium- and late- start groups. We hypothesized that the early-start group would show a larger benefit (decrease) as assessed by the modified Ashworth scale (MAS, primary endpoint) on elbow plus wrist flexors compared with the late-start group. Results: Of the 303 patients enrolled, 292 (96.4%) received ≥1 treatment and 186 (61.4%) received 4 injection cycles and completed the study. Patients in all groups showed a reduction in MAS scores from baseline over the consecutive injection visits (i.e. at end of each cycle). Although reductions in MAS scores descriptively favored the early treatment group, the difference compared to the late group did not reach statistical significance at the last study visit (ANCOVA: difference in adjusted means of 0.15, p=0.546). Conclusions: In this observational, routine-practice study, patients in all groups displayed a benefit from abobotulinumtoxinA treatment, supporting the effectiveness of treatment for patients at various disease stages. Although the data revealed some trends in favor of early versus late treatment, we did not find strong evidence for a significant benefit of early versus late start of treatment in terms of reduction in MAS scores.